Assembly strategies for polyethylene-degrading microbial consortia based on the combination of omics tools and the “Plastisphere” - Zhang, Chengxiao; Mu, Yulin; Li, Taihua; Jin, Feng-Jie; Jin, Chun-Zhi; Oh, Hee-Mock; Lee, Hyung-Gwan; Jin, Long (Frontiers in Microbiology, 2023)
Numerous microorganisms and other invertebrates that are able to degrade polyethylene (PE) have been reported. However, studies on PE biodegradation are still limited due to its extreme stability and the lack of explicit insights into the mechanisms and efficient enzymes involved in its metabolism by microorganisms. In this review, current studies of PE biodegradation, including the fundamental stages, important microorganisms and enzymes, and functional microbial consortia, were examined. Considering the bottlenecks in the construction of PE-degrading consortia, a combination of top-down and bottom-up approaches is proposed to identify the mechanisms and metabolites of PE degradation, related enzymes, and efficient synthetic microbial consortia. In addition, the exploration of the plastisphere based on omics tools is proposed as a future principal research direction for the construction of synthetic microbial consortia for PE degradation. Combining chemical and biological upcycling processes for PE waste could be widely applied in various fields to promote a sustainable environment.